Enhanced spray and evaporation model with multi-fuel mixtures for direct injection internal combustion engines. (June 2014) - Kwak, Kyoung Hyun; Jung, Dohoy; Borgnakke, Claus
A spray and evaporation model has been developed and embedded in a quasi-dimensional multi-zone direct injection internal combustion engine simulation framework. The model accounts for the behavior of the spray zone and fuel evaporation including sub-models for spray breakup, improved zone velocity estimations with transient fuel injection, spray penetration and tracking of evaporated fuel components. Each sub-model deals with multi-component fuel surrogates to simulate the real fuel effects. To enhance sensitivity of the model to the fuel components, additional thermophysical properties to the traditional spray model are incorporated. The ideal gas and the ideal solution are assumed in the model to retain computational efficiency. Finally, the model was validated against experiments and compared with other numerical methods. The ability of the new model to treat a multi-component fuel provides an improvement in the simulations of modern direct injection internal combustion engine when used with alternative fuels.